(untitled) (Journal of Forestry, 2025)
This research aimed to determine the antioxidant activity and total phenolic composition of fresh leaves of Sempervivum tectorum concerning provenance from urban and rural environments. Fresh leaves of the houseleek plant material were collected on a sunny day in June 2024. The homogenized sample was then subjected to maceration extraction at room temperature using distilled water and aqueous solutions of ethanol 70 % and 50 % and methanol 70 % and 50 %. The total phenol content was determined by the Folin-Ciocalteu method, and the antioxidant activity was evaluated by the DPPH "scavenging" method and expressed using the Trolox standard as an equivalent (µmol TE/g). The proportion of total phenols ranged from 42,91 ± 0,83 to 115,96 ± 0,48 mg GAE/g, depending on the type of solvent used and the origin of the plant material. The highest values of antioxidant activity were shown by the methanol extract with a value of 672,51 ± 2,47 µmol TE/g, and the lowest values were shown by aqueous extracts of plant material of both origins. The houseleek samples from higher altitudes showed exceptional antioxidant activity with values from 672,51 ± 2,47 to 359,79 ± 3,97 µmol TE/g, while the samples collected at lower altitudes showed a lower ability to remove radicals according to the DPPH method with values from 366,86 ± 6,91 to 232,78 ± 4,55 µmol TE/g. Using multiple linear regression, it was shown that provenance (β = -0,64; t = -3,167; 0,0016 < 0,05) and solvent (β = 0,552; t = 2,734; 0,029 < 0,05) are significant predictors of the total phenol content for the analyzed samples. Provenance (β = 0,78; t = 4,55; 0,003 < 0,05) and solvent (β = -0,422; t = 2,445; 0,044 < 0,05) are also significant predictors for the antioxidant activity results of the analyzed samples. The result of the t-test showed that there is a statistically significant difference (0,013 < 0,050) in antioxidant activity regarding the provenance of the plant material (urban/rural).